2017
DOI: 10.1016/j.neuroimage.2017.08.058
|View full text |Cite
|
Sign up to set email alerts
|

The EEG microstate topography is predominantly determined by intracortical sources in the alpha band

Abstract: Human brain electric activity can be measured at high temporal and fairly good spatial resolution via electroencephalography (EEG). The EEG microstate analysis is an increasingly popular method used to investigate this activity at a millisecond resolution by segmenting it into quasi-stable states of approximately 100 ms duration. These so-called EEG microstates were postulated to represent atoms of thoughts and emotions and can be classified into four classes of topographies A through D, which explain up to 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
126
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(142 citation statements)
references
References 53 publications
14
126
2
Order By: Relevance
“…They found that these oscillatory indices, and their corresponding neural source estimations, were associated with memory span and working memory performance, as calculated from a switch-cost score from the Test of Attentional Performance. Alpha oscillatory power and LRTC quantify similar phenomena to those of microstate dynamics, given that oscillations in the alpha frequency largely determine the periodicity and spatial distribution of microstates in the broadband EEG (Javed et al, 2019;Milz et al, 2017;Wegner et al, 2017). It would be instructive for future studies to more clearly establish functional connections among these various methods.…”
Section: Discussionmentioning
confidence: 99%
“…They found that these oscillatory indices, and their corresponding neural source estimations, were associated with memory span and working memory performance, as calculated from a switch-cost score from the Test of Attentional Performance. Alpha oscillatory power and LRTC quantify similar phenomena to those of microstate dynamics, given that oscillations in the alpha frequency largely determine the periodicity and spatial distribution of microstates in the broadband EEG (Javed et al, 2019;Milz et al, 2017;Wegner et al, 2017). It would be instructive for future studies to more clearly establish functional connections among these various methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, within-subject fluctuations in the spatial and temporal distribution of dominant EEG spectral power have been systematically associated with the momentary presence of particular microstates (Milz et al, 2017).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…To date, only two groups have utilized this direct approach (Custo et al, in press;Milz et al, 2017; In a recent study (Milz et al, 2017), the same group demonstrated that such activation primarily occurred within the alpha frequency range. However, in contrast to the EEGfMRI studies described earlier, (Pascual-Marqui et al, 2014) and (Milz et al, 2017) did not distinguish the microstate networks based on their temporal signature, but rather focused on the spatial characteristics of the potential fields. Custo and colleagues utilized a source localization approach that more closely resembled the GLM approach used in the EEG-fMRI study by Britz and colleagues .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The neural sources underlying microstates are still being 105 explored Milz et al, 2017;Pascual-Marqui et al, 2014). Still, the dynamics of the 106 sequence of microstates itself can be seen as a "syntax" of neural activity that is in and of itself an 107 .…”
mentioning
confidence: 99%